La gamificación y su incidencia en el aprendizaje cognitivo en niños del subnivel 2 de la Escuela Autora Estrada y Ayala - Arias Jimenez, Mirian Isabel (2022)
The case study work entitled: gamification and its impact on cognitive learning in children of sublevel 2 of the Autora Estrada y Ayala School, which was based on observing the factors that affect or generate the gamification technique in students. And how this influences cognitive learning in the group of students chosen for this case. Especially in transferring game mechanics to learning techniques to achieve better results or assimilate better knowledge, improve certain skills or reward certain activities and be able to make a contribution with data that can be used by teachers to guarantee better learning in students of this initial level. In this study, a variety of data collection techniques and instruments were used, direct observation, and basic monitoring to obtain data on the game model, it really works because it motivates students and achieves cognitive learning. For the preparation of the report, the objective was proposed, proceeding to statistically analyze the data obtained, thus being able to establish the corresponding conclusions.